Quality of life evaluation in patients with locally advanced breast cancer (luminal type B) depending on routes of polychemotherapy administration - O. Bondar (Journal of Education, Health and Sport)
Article outlines that patients’ with locally advanced breast cancer quality of life is significantly correlated with the chemotherapy method and the level of tumour proliferative activity (Ki-67 index). Patients who received selective intraarterial polychemotherapy had higher quality of life indexes at all stages of treatment, especially with a high level of Ki-67. This is probably due to a faster clinical effect, reduction of tumour size and early achievement of resectability. In contrast, in the group with systemic polychemotherapy with high Ki-67, manifestations of general intoxication, lack of subjective improvement in the early stages of treatment and, accordingly, lower quality of life assessments were more often recorded. Thus, combining quality of life data with tumour molecular biological characteristics (the Ki-67 level) can serve not only as a tool for treatment efficacy evaluation but also as an additional predictor for therapeutic strategy choosing which contributes to the personalization of treatment in oncology. This approach allows to improve the quality of medical care, the efficacy of doctor-patient communication and patients with locally advanced breast cancer treatment final results.